A passion for DNA : genes, genomes, and society : with an introduction, afterword, and annotations by Walter B. Gratzer - Watson, James D., 1928- (Oxford University Press, 2000)
In 1953, two young scientists sparked a revolution. James Watson and Francis Crick deduced the molecular composition of DNA and immediately realized that the structure implied how genes were copied and passed on from one generation to the next. Their observation had extraordinary consequences; the discovery of a genetic code; the ability to alter an organism's genetic make-up; new ways of fighting disease; and the means of cloning plants and animals. Nobel Prize-winner, James Watson, has long been a commentator on DNA science and its implications for society. In essays and lectures he delivered dispatches from the front lines of the revolution. Collected here is a selection of these outspoken and topical pieces, mingling with memoirs of distinguished former colleagues, advice for young scientists, and a pointed account of Germany's troubled historical relationship with genetics. Augmented by elegant commentaries from the distinguished molecular biologist Walter Gratzer, this volume portrays the thoughts and work of an intellectual leader of the twentieth century.